Superconformal baryon-meson symmetry and light-front holographic QCD - Dosch, Hans Günter; Téramond Peralta, Guy F. de; Brodsky, S. (Physical review. D, Particles, fields, gravitation, and cosmology, 2015)
We construct an effective QCD light-front Hamiltonian for both mesons and baryons in the chiral limit based on the generalized supercharges of a superconformal algebra. The superconformal construction is shown to be equivalent to a semiclassical approximation to light-front QCD and its embedding in anti-de Sitter space. The specific breaking of conformal invariance inside the superconformal algebra uniquely determines the effective confinement potential. The generalized supercharges connect the baryon and meson spectra to each other in a remarkable manner. In particular, the π/b1 Regge trajectory is identified as the superpartner of the nucleon trajectory. However, the lowest-lying state on this trajectory, the π-meson, is massless in the chiral limit and has no supersymmetric partner.
Gesehen am 25.06.2020